(untitled) (Medico Legal Update, 2020)
Background/Objectives: The aging population due to increases of average life expectancy elderly population is perceived a serious problem in the medical sector. The objective of this study was to determine the degree of awareness of pressure ulcer in nurses in charge of pressure ulcer management in medical institutions and to provide basic data for setting guidelines. Method/Statistical Analysis: A survey and analysis were conducted on 40 nurses in charge of nursing care at a nursing hospital. The survey tool was developed by quoting a pressure ulcer prevention management tool developed by Moore and Price. The survey was conducted in a face-to-face manner, explaining the purpose of the study directly. A total of five questions are recognized as pressure ulcer management, and the reliability is Cronbach’s ? = .785 and consisted of a five-point Likert scale. The general characteristics are gender, age, work experience, Education, and hospital size of nursing hospital, with total five questions and reliability being Cronbach’s ? = .654. Findings: “How much do you know about the pressure ulcer?” showed the highest ‘Yes’ of 30%. In the pressure ulcer management knowledge section, “Do you know about changing your bed posture at least every two hours?” showed the highest ‘very yes’ of 82.5%. “Do you know the standard of management when a pressure ulcer occurs?” showed 45.0% of ‘Yes’ and “Do you know the factors involved in the pressure ulcer?” with 47.5%. “Do you know about the relationship between humidity and temperature among the factors involved in the pressure ulcer?” showed 57.5% (23). Improvements/Applications: The results of this study show the degree of pressure ulcer management by nursing hospital nurses in charge of the pressure ulcer management. Knowledge of the pressure ulcers was high, but low awareness of the factors involved in the management standards emerged. It is expected that this data will be used as basic data for setting up education and management measures for the management of the pressure ulcers in the future.